Citra Diri Guru Pendidikan Anak Usia Dini - Agustin Atmaningrum; Nuratthahirah Ansar; Hafan Asfari (INSIGHT: Indonesian Journal Social Studies and Humanities, 2026)
Abstract. Early Childhood Education (ECE) represents a critical developmental foundation during the so-called golden age, in which teachers serve as central role models shaping children's cognitive, social, and emotional development. However, limited professional recognition of ECE teachers in Indonesia remains a significant challenge, potentially affecting their self-image and psychological well-being. This study aimed to examine the effectiveness of psychoeducational intervention in enhancing the self-image of ECE teachers. This research employed a quantitative approach using a one-group pretest–posttest design involving 43 participants. The intervention consisted of four structured psychoeducation sessions addressing the definition, dimensions, influencing factors, and strategies for improving self-image. Data were analyzed using the Wilcoxon Signed Rank Test following the Shapiro–Wilk normality test, which indicated non-normal data distribution. The findings revealed a significant difference between pretest and posttest scores (Asymp. Sig. (2-tailed) = 0.013, p < 0.05). Fourteen participants demonstrated increased scores (positive ranks), twenty-five showed no change (ties), and four exhibited decreased scores. These results indicate that psychoeducation effectively facilitates a shift toward a more adaptive and constructive professional self-perception. Overall, psychoeducation serves as a preventive and promotive intervention to strengthen teachers’ resilience and professional self-concept amid structural challenges.Keywords: Self-image; Early Childhood Education Teachers; Psychoeducation; Golden Age